The role of self-efficacy, entrepreneurial passion, and creativity in developing entrepreneurial intentions - Ferreira-Neto, Macário Neri; de Carvalho Castro, Jessyca Lages; de Sousa-Filho, José Milton; de Souza Lessa, Bruno (Frontiers in Psychology, 2023)
Although studies aimed at understanding entrepreneurship have analyzed passion, creativity, and entrepreneurial self-efficacy, few studies include these antecedents in the same model. In this sense, this study aims to assess the relationship between passion, self-efficacy, and creativity with entrepreneurial intention. The data was collected through a survey and the questionnaires were applied to university students who formed a sample of 190 respondents, and such data was analyzed using structural equation modeling and based on partial minimum least square technique. Regarding our results, t The relationship between creativity and entrepreneurial intention has not been confirmed. The multigroup analysis revealed that the level of education influences men's entrepreneurial intention and creativity only influences entrepreneurial intention when mediated by entrepreneurial passion. This study contributes by highlighting the roles of analyzed passion, creativity, and entrepreneurial self-efficacy in entrepreneurs from one of the largest emerging economies in the world. Moreover, it also contributes to theoryacademia as it confirms the explanatory power of the Theory of Planned Behavior as a tool to understand the cognitive foundations of entrepreneurship. It also offers a practical contribution by signaling to public policymakers which features should be incentivized to boost entrepreneurship in emerging economies.